Running the American CorporationDillWilliam R. (Ed.) Running the American Corporation. Englewood Cliffs, N.J.: Prentice-Hall, 1978, 180 pp., $10.95, paperback $4.95. - Preston, Lee E. (Academy of Management Review, 1979)
This article presents a review of the book ?Running the American Cooperation,? edited by William R. Dill.